Assessment of Malnutrition and Intestinal Parasitoses in the Context of Crisis-Hit Venezuela: A Policy Case Study - Mejias-Carpio, Isis E.; Paniz-Mondolfi, Alberto E.; Mogollon-Rodriguez, Euler A.; Delgado-Noguera, Lourdes A.; Sordillo, Emilia M.; Urbina-Medina, Huniades A.; Hayon, Jesica; Vetencourt-Pineda, Leonardo A.; Perez-Garcia, Luis A. (Frontiers in Sustainable Food Systems, 2021)
Venezuela is in the midst of a humanitarian crisis with a dangerous cocktail of hyperinflation, violence, minimal local food production, and policies that impact the nutrition for millions of Venezuelans. Independent data suggests that most Venezuelans are food insecure, with alarming rates of acute and chronic malnutrition, especially among children. A re-emergence of poverty-related intestinal parasitoses and anemia has aggravated their health. With little to no response from public authorities, Venezuela is now the lowest-ranked country in the world in deworming coverage. Modest independent and private epidemiological studies suggest prevalence rates as high as 60% in some regions. This article reviews public health policies regarding malnutrition and intestinal parasitoses and aims to provide a rational approach based on international recommendations for countries in crisis.